PENINGKATAN HASIL BELAJAR PKN MELALUI MEDIA GAMBAR SISWA KELAS V SD NEGERI 05 SIALANG KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - Arni Arni (Ensiklopedia Education Review, 2019)
The background of the problem of this research is that the learning process is felt to still need to use media. The condition of learning causes students to be more enthusiastic about learning and can quickly understand the material delivered by the teacher. The purpose of this study was to describe the Improvement of Student Learning Outcomes in Class V of Sialang 05 Elementary School in Kapur IX District, Lima Puluh Kota District through media images. This research is Classroom Action Research. The subjects of the study were the fifth grade students of Sialang 05 Elementary School in Kapur IX District as many as 29 students consisting of 13 women and 16 men. The instruments in this study are: observation, testing and documenting. Data analysis techniques in the main activities of this model analysis include among others (1) data analysis of observation sheets of teacher and student activities, and (2) analysis of student learning outcomes. Observation is used to determine the teacher's ability to manage the learning and activities of students in the learning process by using media images. The results showed that in the first cycle the results obtained were 12 students 42% above the KKM and in the second cycle 26 students were 90% above the KKM. So, based on the results of the study show that there is an increase from cycle I to cycle II. Suggestions to teachers, especially grade V teachers to use picture media in accordance with the material being taught so as to improve the completeness of student learning outcomes.